The misadventures of Winnie the Witch - Owen, Laura; Paul, Korky (Winnie and Wilbur., 2018)
Winnie is full of mad-cap schemes and plans to put her magic to good use. Wilbur is her long-suffering best friend, and everyone's favourite moggy. From Winnie's knicker shop, where spiders sew up the lacy trims, to Winnie's creativity in the kitchen where she often cooks up such delicacies as turkey tonsil titbits, giggles are guaranteed!